The Impact of pH Preparation on the Physical Nature and Metal Phase of Zeolite-Supported Metal Catalyst - Nugrahaningtyas, Khoirina Dwi; Budiman, Anatta Wahyu; Sabiila Gusti, Aji Indo; Heraldy, Eddy; Hidayat, Yuniawan (Jurnal Riset Kimia, 2024)
The synthesis of CoMo/USY catalysts has been widely carried out. However, the bond strength between metal and USY is still a problem. Therefore, this research has synthesised the catalyst with the chelating agent ethylenediaminetetraacetate (EDTA). Apart from that, the effect of pH on the characteristics of the catalyst is also reviewed. This research aims to analyse the effect of preparation pH on catalyst characteristics. In the preparation process, the pH of the solution is set at values of 2, 7, and 8. Catalyst activation includes a calcination process and reduction. The catalyst characterisation uses XRD, GSA, and FTIR instruments to determine phase composition, specific surface area, and functional groups. The result showed that pH preparation significantly influenced the metal loading on the catalyst and reached a maximum at pH 8. The surface area is not directly related to the pH of the preparation but has the opposite property depending on the amount of metal added. Meanwhile, it was found that the CoO and MoO3 phases were achieved on the catalyst by all pH preparations. On the other hand, the CoMo alloys are present on the catalyst at pH 7 and 8, while the Co and Mo elements are visible at pH 2. The difference in pH during the synthesis process impacts the shift in the absorption wave number of the OH vibration.